SPIRIT DAN ENERGI SOSIAL PEREMPUAN MADURA, DALAM KONTEKS PERUBAHAN SOSIAL - Sukesi, Keppi; Wisaptiningsih, Umi; Nurhadi, Iwan (Jurnal Interaktif, 2010)
This research aims to: 1) identify and analyze spirit of Madurese women to do the productive and domestic work; 2) analyze dominant and intrinsic behavior of Madurese woman in household economy; 3) analyze the perception of Madurese women to social change, economy and traditional institute.Qualitative approach were conducted as research method and population of study was Madurese women, both, who live in Madura Island and outside Madura Island (migrant). Research location selected purposely in Pamekasan, City of Malang and Southside of Malang Residence. Case study method was used exhaustively combined with historical approach and census document and also with focus group discussion with Madurese women. Informants was selected to depict various characteristicsÂ  and was traced by snowball system. Data intake was conducted with 1) Structured Interview; 2) Observation; 3) group interview; d) understanding symbolic value and myth. The data analyzed by descriptive qualitative method.The research conclusion showed that spirit of Madurese woman from various coat as an inhabitant or a migrant show the high spirit which supported by accomplished working ethos. This ethos was resulted by requirement of religious service, independence and obligation. The Migration of Madurese women was influenced by coush to prove their life quality. Potential local institution is assisting the women work in marionette pesantren, tanean lanjeng, and agriculture institution and commerce. Spirit of Madurese woman the eager beaver is pushed by social energy of migrating behavior and powered by the will to increase to increasing the family life quality. This research needs to be continuied to find comprehensive local knowledge of the women executed by circumstantial study and focused discussion on working activity and local adaptation ethic.Keyword: Social Energy, Madurese Woman